Metabolic reprogramming and lipid droplets are involved in Zika virus replication in neural cells - Dias, Suelen Silva Gomes (2023)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunofarmacologia. Rio de Janeiro, RJ, Brasil.